Analysis of the importance of supporting students with special educational needs: A review article - Chavarry, Madelaine Rosa Peña; Alvarez, Carlos Alberto Villafuerte; Flores, Moisés Oswaldo Farfán; Guzman, Yessenia Bernales (Edelweiss Applied Science and Technology, 2025)
The objective of this study was to analyze the importance of supporting students with Special Educational Needs (SEN) by identifying and systematizing scientific evidence from the period 2022-2025. To conduct this analysis, a systematic literature review was carried out using the PRISMA approach, providing a methodological framework that included national and international policies, pedagogical approaches, and inclusive frameworks. This contributed to the validity and reliability of the findings, promoting the replicability of the results and ensuring the transparency of the selection processes. After applying inclusion and exclusion criteria, 24 relevant works were addressed, offering a comparative overview of inclusive strategies while considering regulatory provisions and emerging practices. Among the results, Universal Design for Learning, curricular adaptation, and collaborative work were highlighted as emerging practices. The research concludes by stating that the integrated application of these inclusive practices significantly enhances the participation of students with SEN.